Research on tombs and burials from the pre-mongol empire period (Studia Archaeologica, 2025)
Archaeological sites dating to the pre-Mongol Empire period are extremely rare. Burial sites as sociated with the Mongols from the end of the Uyghur period are particularly scarce, with only a few graves having been excavated accidentally. The Ereen Tolgoi burial site, located in Dadal soum, Khentii aimag, was excavated by our research team in 2021 and 2024, reveals a Mongol tomb from the Khitan period. The funeral rituals at the Ereen Tolgoi cemetery are characterized by the deceased being laid on their right side, with the head oriented towards the northeast, east, or southeast, and the legs slightly bent at the knees. These burials are accompanied by ritual elements associated with beliefs of the afterlife, including a small cattle palm bone and a knife.Монголын эзэнт гүрний өмнөх үеийн булш, оршуулгын судалгаа Хураангуй: Монголын Эзэнт гүрнээс өмнөх үеийн монголчуудтай холбогдох археологийн дурсгал бага судлагдсан бөгөөд одоогоор зарим нэг санамсаргүй байдлаар малтсан Уйгурын төгсгөл, Хятаны үеийн монголчуудын оршуулгын дурсгал байна. Бидний судалгааны баг 2021, 2024 онд Хэнтий аймгийн Дадал сумын Эрээн толгойн оршуулгын дурсгалд малтлага судалгаа хийсэн бөгөөд энэ нь Хятаны үеийн монголчуудын булш юм. Эрээн толгойн оршуулгын газрын оршуулгын зан үйлийн онцлог нь талийгаачийг голдуу зүүн гурван зүгт толгойг нь хандуулах бөгөөд баруун хажуугаар нь хэвтүүлээд, хөлийн өвдгийг нь бага зэрэг нугалан оршоож, үүнд хойд насны идээ болгож заавал богийн дал, хутга дагалдуулах онцлогтой. Түлхүүр үг: Өвөг Монгол, оршуулгын зан үйл, булш, дал, хутгаRevised some words of abstract dated on 2025-09-18